2018
DOI: 10.1002/2018jc013821
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment and Energy Transfer Variability Along the Descending Path of the Denmark Strait Overflow Plume

Abstract: The descent of the Denmark Strait overflow plume is an important process in the Atlantic Meridional Overturning Circulation. Downstream of the sill, the plume entrains ambient water, increasing its volume transport. The entrainment and related transfer of energy can be driven by vertical or horizontal turbulent mixing, and varies spatially, as the plume descends, and temporally, as the volume transport at the sill changes. Using over 30 years of profile data, this spatial and temporal variability in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Having resolved L T as an indicator of vertical mixing, it is possible to then derive an estimate of turbulence dissipation rate from the overturning length scale (Moum, 1996): Dillon (1982). This ratio has been supported by subsequent observations (Ferron et al, 1998;Moum, 1996;Paka et al, 2013;Stansfield et al, 2001) and is commonly used to infer in the ocean due to the relative ease with which overturns are measured using standard oceanographic instrumentation (Finnigan et al, 2002;Fer, 2004;North et al, 2018). However, a number of other studies have proposed coefficients ranging from 0.6 to 1.2 (Mater et al, 2015;Smyth, 2000) and Ferron et al (1998) found that variability in the ratio can be 60%.…”
Section: Methodsmentioning
confidence: 89%
“…Having resolved L T as an indicator of vertical mixing, it is possible to then derive an estimate of turbulence dissipation rate from the overturning length scale (Moum, 1996): Dillon (1982). This ratio has been supported by subsequent observations (Ferron et al, 1998;Moum, 1996;Paka et al, 2013;Stansfield et al, 2001) and is commonly used to infer in the ocean due to the relative ease with which overturns are measured using standard oceanographic instrumentation (Finnigan et al, 2002;Fer, 2004;North et al, 2018). However, a number of other studies have proposed coefficients ranging from 0.6 to 1.2 (Mater et al, 2015;Smyth, 2000) and Ferron et al (1998) found that variability in the ratio can be 60%.…”
Section: Methodsmentioning
confidence: 89%
“…High‐resolution modeling studies could provide answers, although topographic features may very well play a role, which are a challenge to capture realistically in models. The lifetime, pathway, and dissipation of the sill eddies will be addressed in further studies, eventually linking the features to downstream overflow modification (North et al, ) and eddy features off Greenland (von Appen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Price and Baringer 1994;Legg 2012). Although the mixing in overflows is highly localized (North et al 2018), it plays a significant role in influencing the largescale ocean circulation (Koszalka et al 2017). Studying the DSO helps us understand common features of climatologically important overflow processes in other parts of the global ocean.…”
Section: Introductionmentioning
confidence: 99%